Lipocalin-2 and Cerebral Stroke - Luo, Chao; Zhou, Shuai; Yin, Shi; Jian, Lipeng; Luo, Pengren; Dong, Jigeng; Liu, Erheng (Frontiers in Molecular Neuroscience, 2022)
Stroke is a common and devastating disease with an escalating prevalence worldwide. The known secondary injuries after stroke include cell death, neuroinflammation, blood-brain barrier disruption, oxidative stress, iron dysregulation, and neurovascular unit dysfunction. Lipocalin-2 (LCN-2) is a neutrophil gelatinase-associated protein that influences diverse cellular processes during a stroke. The role of LCN-2 has been widely recognized in the peripheral system; however, recent findings have revealed that there are links between LCN-2 and secondary injury and diseases in the central nervous system. Novel roles of LCN-2 in neurons, microglia, astrocytes, and endothelial cells have also been demonstrated. Here, we review the evidence on the regulatory roles of LCN-2 in secondary injuries following a stroke from various perspectives and the pathological mechanisms involved in the modulation of stroke. Overall, our review suggests that LCN-2 is a promising target to promote a better understanding of the neuropathology of stroke.